Answer:
four glorps
Explanation:
We know :
[tex]$y=v_{0y}t + \frac{1}{2}a_yt^2$[/tex]
[tex]$\Rightarrow -1 \text{glorp} = 0 - \frac{g}{2} \times (1 g\text{ gleep})^2$[/tex]
[tex]$\Rightarrow 1 \text{ glorp}= \frac{g}{2} (1 \text{ gleep})^2$[/tex] .............(i)
Now, t' = 2 gleep
[tex]$y=v_{0y}t + \frac{1}{2}a_yt^2$[/tex]
[tex]$=0+ \frac{-g}{2} (2 \text{ gleep})^2$[/tex]
[tex]$=-\frac{4g}{2}(2 \text{ gleep})^2$[/tex]
[tex]$=4\left[\frac{-g}{2} (\text{gleep})^2\right]$[/tex]
= 4 (-1 gleep) (From (i))
So, |y| = 4 glorp